Graduate Work Skill - Salem, Ahmed Moftah Emhamed (2009)
One purpose of higher education is to graduate students who will become productive citizens. Some researchers are suggested that every member of an institution of higher education is responsible for promoting educationally purposeful activities that lead to producing good citizens. They argued that students, faculty, administrators, and staff should attempt to prepare students for productive lives after college. There are various ways that students can learn these skills. However, they can be learned in the classroom, and through extracurricular activities and etc. This present study is investigated if accounting graduates from University Utara Malaysia College of Business, a public institution, perceived that their accounting curriculum enhanced the development of their personal competencies of professional demeanor, accounting knowledge, auditing knowledge , computer knowledge, economics, law, leadership,logical reasoning, memorization, oral communications, professionalism, problem solving, statistics, time management, written communications, and working well with others. A survey of accounting graduates who in final semester of program of master together the data of this study. Responses from the students with different curricular paths were compared to determine if significant differences existed in their perceptions of the development of their personal competencies.